CD62L is not a reliable biomarker for predicting PML risk in natalizumab-treated R-MS patients. (26th January 2016) - Lieberman, Linda A.; Zeng, Wanyong; Singh, Carol; Wang, Wenting; Otipoby, Kevin L.; Loh, Christine; Plavina, Tatiana; Gorelik, Leonid; Ransohoff, Richard M.; Cahir-McFarland, Ellen
Abstract : Objective: To assess if the percentage of CD3 + CD4 + CD62L + cells in cryopreserved peripheral blood mononuclear cells (PBMCs) (here termed %CD62L) can predict risk of developing progressive multifocal leukoencephalopathy (PML) and better inform the physician for benefit–risk assessment of natalizumab treatment decisions in a global setting. Methods: Cryopreserved PBMCs from 21 natalizumab-treated patients who developed PML and 104 matched natalizumab-treated patients with multiple sclerosis (MS) without PML collected as a part of Biogen clinical trials were retrospectively examined for CD3, CD4, CCR7, CD45RA, and CD62L by flow cytometry. Results: In this cohort, %CD62L in natalizumab-treated patients did not predict PML risk. Natalizumab-treated patients with MS without PML showed highly variable %CD62L upon serial sampling. In the STRATA study, the distribution of %CD62L in samples collected more than 6 months before a PML diagnosis, at diagnosis, and in natalizumab-treated patients without PML overlapped. No statistical threshold for risk could be determined. In addition, we demonstrated that lymphocyte viability strongly affects %CD62L, supporting previous reports that %CD62L is inherently unstable following cryopreservation and is sensitive to sample collection. Conclusion: Data from this well-controlled cohort of natalizumab-treated patients indicate that %CD62L is not a biomarker of PML risk.